The Process of Development Among Counsellor Interns: Qualitative and Quantitative Perspectives - Rak, Carl F.; MacCluskie, Kathryn C.; Toman, Sarah M.; Patterson, Lewis E.; Culotta, Susan (Canadian Journal of Counselling and Psychotherapy, 2007)
This pilot study examined qualitative and quantitative changes in counselling interns' skill development and perceptions of their own development over the internship year. Eighteen counselling interns completed a pre- and post- internship questionnaire, and of those interns, twelve submitted three videotaped counselling sessions, taped at the beginning, middle, and end of the internship. Videotapes were analyzed based upon Bloom's (1986) theory of automaticity. Responses to the questionnaires were subjected to a qualitative content analysis. The longitudinal data reflected aspects of the theoretical developmental model proposed by Stoltenberg and Delworth (1982). Implications for counsellor internship training are discussed.